Electrical Properties of 1-3 Piezocomposites Prepared from Textured KSr2Nb5O15 (KSN) Ceramic Fibers - Dursun, Sinan; Alkoy, Sedat (Taylor & Francis Ltd, 2011)
Highly [001] textured KSr2Nb5O15 (KSN) ceramic fibers were fabricated by a combination of novel alginate gelation method and templated grain growth using acicular KSr2Nb5O15 template particles. Fibers were drawn from alginate based slurries without or with 10 wt% KSN template particles. A maximum texture fraction of 0.96 was obtained. Piezocomposites with 1-3 connectivity were prered from the KSN fibers and their electrical and electromechanical properties were investigated. Dielectric constant of 90, piezoelectric charge coefficient of 60 pC/N, remnant polarization of 10 mu C/cm(2) and electric field induced strain of up to 0.036% were obtained from piezocomposites with textured fibers.
Joint Meeting of the 19th IEEE International Symposium on the Applications of Ferroelectrics/10th European Conference on the Applications of Polar Dielectrics -- AUG 09-12, 2010 -- Edinburgh, SCOTLAND
Keywords: KSN; texture; fiber; piezocomposite